MÜNCHAUSEN SYNDROME - A QUESTION OF MEDICAL ETHICS? - Daniela Pacurar; Gabriela Lesanu; Anca Popescu; Irina Dijmarescu; Dumitru Oraseanu (Amaltea Medical Publishing House, 2017)
"Factitious disorder" or "unnatural, artificial, fake disorders" as Münchausen syndrome (MS) and Münchausen syndrome by proxy (MSBP) represent severe mental disorders in which a person tries to convince those around him/her that he/she or the person depending on him/her is sick, without the purpose of obtaining benefits. Patients with disorders such as MS or MSBP may arise a series of controversies and appeals from the simple question of patient status to confidentiality issues, privacy, medical malpractice or participation and involving of the medical team at the suffering of the patient. Recognition of the phenomenon of simulation depends heavily on experience of the physician, but the existence of elements of guidance and personality traits of patients or parents are important. Many issues of ethics and medical deontology arise in diagnosis, evolution and treatment of these syndromes, many becoming subject to medical or legal disputes. The problem is more delicate and involves many consequences in terms of child protection in MSBP, considered the only form of lethal, highly complex mistreatment and abuse. Ethical, medical and ethics issues are different in the two types of diseases, but medical staff involvement and participation in perpetuation of the symptomatology is a common character, much debated. Despite the controversy, many of these issues remain unresolved and there are no clear guidelines so doctors can give an appropriate response.